Enhancement of permittivity off-diagonal terms in rare earth transition metal / heavy metal hetero-structured films - Matsumoto, Kei; Thach, Pham Van; Sumi, Satoshi; Ranjbar, Sina; Tanabe, Kenji; Awano, Hiroyuki; Wang, Shihao; Ishibashi, Takayuki; Saito, Shin (Frontiers in Physics, 2022)
The SHE (spin Hall effect), DMI (Dzyaloshinskii-Moriya interaction), Rashba effect, etc. are extremely important effects for the development of the conduction phenomenon of spin electronics due to the breaking of the spatial inversion symmetry of the hetero interface made of heavy metals such as Pt and W. These are due to SOI (spin-orbit interaction). Most of these studies have been conducted in the frequency domain below GHz, and there are few studies in the energy domain of light. Therefore, in the region of light energy, the magnetic optical Kerr effect spectra of the TbCo/Pt hetero-structured film with large SOI from the Pt interface and the TbCo/Cu hetero-structured film with small SOI from the Cu interface were measured, and the permittivity tensors were investigated respectively. As a result, in the TbCo / Pt hetero-structured film, the dielectric constant off-diagonal component real part of the thin TbCo layer increased about twice as much as that of bulk TbCo in the energy region smaller than 2.5 eV. However, this increase was not observed in the TbCo / Cu hetero-structured film. This result suggests that the influence of the Pt hetero interface where the spatial inversion symmetry is broken may appear even in the energy region of light. Furthermore, it has been confirmed that TbCo / W hetero-structured film using W with a large SOI has the same increasing effect as that of the TbCo / Pt.